The Significance of Financial Performance Indicators on Stock Price: Evidence from PT Selamat Sempurna Tbk - Agustin, Rista Talia; Octovian, Reza (Indonesian Financial Review, 2025)
This study aims to determine the Effect of Return on Investment, Return on Equity and Dividend Payout Ratio on the Stock Price of PT Selamat Sempurna Tbk for the 2014-2023 Period. This study uses a quantitative method with a descriptive approach. The data analysis methods used are descriptive statistical tests, classical assumption tests (normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests), multiple linear regression analysis, determination coefficient tests, and hypothesis tests (t-tests and f-tests) processed through the SPSS (Stastical Product and Service Solution) version 27 program. The results show that Return on Investment (ROI) has a significant negative effect, Return on Equity (ROE) has a positive effect, and Dividend Payout Ratio (DPR) has a negative effect on the stock price of PT Selamat Sempurna Tbk during 2014–2023.